Fatigue characteristics and microcosmic mechanism of Al-Si-Mg alloys under multiaxial proportional loadings - Jiang, Xiao-song; He, Guo-qiu; Liu, Bing; Zhu, Zheng-yu; Zhang, Wei-hua (International journal of minerals, metallurgy and materials, 2011)
With the increasing use of Al-Si-Mg alloys in the automotive industry,the fatigue performance of Al-Si-Mg alloy has become a major concern with regard to their reliability.The fatigue characteristics and microcosmic mechanism of an Al-Si-Mg alloy under multiaxial proportional loadings were investigated in this research.As low cycle fatigue life and material strengthening behavior are closely related,the effect of equivalent strain amplitude on the multiaxial fatigue properties was analyzed.Fatigue tests were conducted to determine the influence of equivalent strain amplitude on the multiaxial proportional fatigue properties.The fatigue life exhibits a stable behavior under multiaxial proportional loadings.The dislocation structures of the Al-Si-Mg alloy were observed by transmission electron microscopy（TEM）.The dislocation structure evolution of the Al-Si-Mg alloy under multiaxial proportional loadings during low cycle fatigue develops step by step by increasing fatigue cycles.Simultaneously,the dislocation structure changes with the change in equivalent strain amplitude under multiaxial proportional loadings.The experimental evidence indicates that the multiaxial fatigue behavior and life are strongly dependent on the microstructure of the material,which is caused by multiaxial proportional loadings.